2013
DOI: 10.1007/s00431-013-2177-2
|View full text |Cite
|
Sign up to set email alerts
|

The association of vitamin D status with cardiometabolic risk factors, obesity and puberty in children

Abstract: The association between vitamin D status and BMI is complex, and it does not seem to be altered by mild obesity. In addition, potential influence of puberty should be kept in mind while assessing the relationship between serum 25(OH)D and cardiometabolic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 62 publications
4
35
0
4
Order By: Relevance
“…As in our results, some other studies have shown negative associations between pubertal status and serum 25(OH)D concentration in both sexes (15,18,37,38) , although increasing age, lesser outdoor sport and greater demands on vitamin D stores for skeletal mineralization could contribute to this finding (17,39) . It is necessary to consider pubertal stage as it is associated with a remarkable change in the lifestyle of children in terms of daily sun exposure and outdoor physical activity; clothing and percentage of body surface area exposed may contribute significantly to change in 25(OH)D concentration in this stage (40) .…”
Section: Pubertysupporting
confidence: 44%
“…As in our results, some other studies have shown negative associations between pubertal status and serum 25(OH)D concentration in both sexes (15,18,37,38) , although increasing age, lesser outdoor sport and greater demands on vitamin D stores for skeletal mineralization could contribute to this finding (17,39) . It is necessary to consider pubertal stage as it is associated with a remarkable change in the lifestyle of children in terms of daily sun exposure and outdoor physical activity; clothing and percentage of body surface area exposed may contribute significantly to change in 25(OH)D concentration in this stage (40) .…”
Section: Pubertysupporting
confidence: 44%
“…Many obese children present with low blood concentrations of vitamin D [79], probably due to its insufficient dietary intake and too small amount of outdoor physical activity [10, 11]. Also greater fat mass seems to be associated with lower blood concentration of vitamin D, which may, at least partially, result from sequestration of this vitamin in adipose tissue [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies documented inverse relationships between blood concentration of vitamin D, waist circumference, systolic blood pressure, insulin resistance, fasting glycaemia, total cholesterol, triglyceride and LDL cholesterol levels in paediatric subjects, as well as positive associations between concentrations of vitamin D and HDL cholesterol [7, 14, 15]. Vitamin D seems to interfere with insulin secretion both directly, binding to its receptors (VDR) on pancreatic β cells, and indirectly, modulating extracellular concentration of calcium [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a large-scaled study involving 2,488 adults, both seasonal variation and severe deficiency were detected (14). In a small-scaled study involving 391 individuals, a statistically significant relationship was reported between cloths and deficiency (15).…”
Section: Resultsmentioning
confidence: 94%